The Influences of Transaction Costs on Dairy Farming system in South Sulawesi Province - S. N. Sirajuddin; H. Siregar; B. Juanda; A. H. Dharmawan (Jurnal Ilmu dan Teknologi Peternakan, 2011)
The research aimed to 1) identify transaction cost in small holder dairy farm operating either under partnership or independent system, 2) analyze the influence of transaction cost for dairy cattle business system, in South Sulawesi. The research was carried out from November 2009 to March 2010 at two different regions based on the farming system practiced, namely for partnership system in Sinjai Regency and for independent system in Enrekang Regency. Descriptive analysis was applied to identify the first aim of study and the logic model was adopted to analyze the second one. For the latter, 30 farmers for each system were deeply interviewed. The results of this research showed that (1) transaction cost of partnership system was lower than that of independent system, (2) transaction cost, particularly transportation cost, had significant influence on partnership system.